Peran Dinas Kependudukan dan Pencatatan Sipil dalam Pemenuhan Hak Administrasi Kependudukan bagi Penyandang Disabilitas di Kabupaten Sidoarjo - Maise Ismandar; Muhammad Farid Maruf; Galih Wahyu Pradana; Melda Fadiyah Hidayat (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
Innovative service programs are still unable to ensure that all administrative rights related to civil registration are properly fulfilled, especially for vulnerable groups such as people with mental disorders and persons with disabilities. This study aims to examine the role of the Sidoarjo District Population and Civil Registration Office in fulfilling the administrative rights of the community, identify factors that facilitate and hinder this process, and evaluate how inclusive public service policies are implemented. This study uses a qualitative approach to understand how inclusive public services are implemented. The study shows that there are obstacles in procedures and administration, particularly in the initial online application process, and that there are no clear SOP documents regulating services for persons with disabilities. In addition, the manner of imposing official sanctions in the implementation of the Peduli Dilan Program is not yet clear. Nevertheless, the Population and Civil Registration Office of Sidoarjo Regency has made efforts to provide inclusive services and focus on fulfilling rights. This study shows that the role of the Population and Civil Registration Office of Sidoarjo Regency is already functioning, but it still needs to be strengthened in terms of resources, data collection systems, and service coverage expansion so that the administrative rights of vulnerable groups can be fulfilled more evenly and sustainably.